Effect of Shape, Size of Pores on Saturated Hydraulic Conductivity of Some Iraqi Soils - Ati, A S.; Kareem, B M. (Sulaimani Journal for Pure and Applied Sciences, 2014)
This study aims to find out the effect of shape, size of pores on saturated hydraulic conductivity. Ten pedons were selected from the north of Iraq; five pedons were selected from Sulamani province: Bakhteari forest, Bazian, Choesoor, Kanakow and Sarsank was from Duhok province. While in the middle sites, five pedons were selected from Baghdad, two from college of agriculture, Al-Tarmia, and Al-Raeed experimental station, the last pedon from Al-Anbar province – Al-Husaenia. Disturbed and undisturbed soil samples were taken from surface and subsurface horizons from each pedon. Some chemical and physical properties were determined, which include texture, carbonate minerals, free iron oxides, organic matter, bulk density, porosity and hydraulic conductivity. Also they were used for micro morphological characterization as thin section and scanning electron microscopy. The results indicated that the highest value of saturated hydraulic conductivity of the northern sites were 77.73cm.hr-1 at P4A1(north), the lowest value was 0.47 and 0.47 cm.hr-1 observed in surface and subsurface horizons of P3 . The high value of middle sites was 9.89 cm.hr-1in P9A1; the lowest value was 0.89 cm.hr-1 in P8C1. Micro morphological characterization showed variation in the shapes and size of pores for all studied horizons. Also, they showed coating and filling material affecting the pores. The dominant shapes were channels, chambers, voids. The results show that there are differences in shapes and size of pores between north and middle sites, where the dominant shapes of pores in middle sites were chamber and packing. The results showed the existence of free iron oxides which increased MWD and bulk density and decrease hydraulic conductivity and porosity; also it's forming type of shape as small chamber. Organic matter forms meta vughs which make the hydraulic conductivity high because this type of shape is more stable.
Keywords: hydraulic conductivity shape and size of pores micro morphological scanningelectron microscopy